صراع قرامطة البحرين مع السلطة البويهية - سعيد، عمر أحمد (جامعة الموصل - كلية التربية الأساسية, 2013)
ظهرت القرامطة في البحرين من سنة (281هـ/894م) وحتى سنة (398هـ/ 1007م) وأخذت علي عاتقها التصدي للبويهيين الذين جاءوا من بلاد فارس متوجهين إلي العراق وسيطروا عليه، ثم أرادوا مد نفوذهم إلي مناطق البحرين معقل القرامطة . وقد وجه البويهيون أنظارهم إلي البحرين لعدة أسباب منها: من أجل توسيع حدود دولتهم بعد أن سيطروا علي بلاد فارس والعراق، لذلك فكروا بضم سواحل الخليج العربي إلي ممتلكاتهم بعد أن تعرضت أملاك السلطة البويهية إلي هجمات عديدة من قبل قرامطة البحرين ولاسيما الإغارة علي قوافل الحجاج مستغلين تدهور العلاقة بين الخلافة العباسية والبويهيين.أما السبب الثاني فظهرت رغبة لدي البويهيين في الحصول علي نصيب وافر من تجارة سواحل الخليج العربي، فقد اتصف الأمراء البويهيون بحب الثروة وجمع الأموال. قسم البحث إلي مبحثين، تناول المبحث الأول القراطمة في البحرين قبل التسلط البويهي (281-332هـ/ 894-944م)، أما المبحث الثاني فكان القرامطة في البحرين في ظل التسلط البويهي (334-398هـ/ 945-1007م). The Garamida appeared in Bahrain from (281 A.H./894 A.D.) and they undertook confronting Buwaid who came from Faris land directed to Iraq, and controling it They wanted then to extend their authority to Bahrain regions the stronghold of Garamida. The Buwyid look forward towards Bahrain, for many reasons, such as extending their borders after they captured the land of Faris and Iraq so they thought of join the costs of the Arab gulf to their properties \ after it faced so many attacks by Bahrain's Gramida, specially the raid onthe pilgrims Caravans exploiting diteiorated the relations between the Abassid caliphat and Buwyids. The second reason was the wish of the Buwaids to gain anabandance share of the Arab Gulf costs trade. The princes of Buwyids were carachtorized by loving the wealth and collecting money. The research is divided into two sections, the first one dealt wih the Gramida in Bahrain before the Buwyids domination (281 - 332 A.H./894 - 944 A.D.), as for the second one, it deals with the Garamida in Bahrain at the Buwyids domination \ (334 - 398 A.H. 1945 - 1007 A.D. ).
Keywords: التاريخ الإسلامي -- الدولة البويهية -- الملوك و الحكام -- القرامطة -- الصراع السياسي -- البحرين